PLusiinae (Excl. Abrostolini) (Lepidoptera: Noctuidae) of Ethiopia. A faunistical survey with biogeographical comments - Kravchenko, Vasiliy D.; Ronkay, Laszlo; Behounek, Gottfried; Müller, Günter C. (Zootaxa, 2015)
The extensive survey in different regions of Ethiopia between 1987–1990 and 2005–2011 resulted in the recognition of 39 species of Plusiinae. The majority of the species belong to two large genera, Ctenoplusia (15 species) and Thysanoplusia (16 species). A new synonymy is established, Plusiotricha gorilla (Holland, 1894) is proved to represent the female sex of Plusiotricha livida Holland, 1894 (syn. nov.). The present paper does not include the records of the species of the tribe Abrostolini. Eighteen species are recorded for the first time from Ethiopia. Twenty species of the identified taxa are known only from tropical and subtropical Africa, while the areas of ten species extend from Africa to the Arabian Peninsula or even further to the north. Eight species are widespread not only in Africa but also in the Palearctic and Oriental regions. One species—Autographa gamma, a well-known Palearctic pest of different vegetables—is found in the Afrotropical region only in Ethiopia, at medium and high mountain elevations but not in the tropical lowlands.